2015
DOI: 10.1063/1.4913471
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing direct magnetoelectric coupling in Pb(Zr,Ti)O3/Ni multiferroic film heterostructures

Abstract: Polycrystalline Pt thin films of different thicknesses (0–75 nm) were introduced using magnetron sputtering in Pb(Zr0.52Ti0.48)O3 (PZT, 400 nm in thickness)/Pt/Ni multiferroic film heterostructures, aimed at optimizing the transfer efficiency of magnetostrictive strain from the bottom Ni foil to the top PZT film and thus the direct magnetoelectric (ME) coupling. The ME voltage coefficient αE31 was directly measured, while the strain transfer efficiency k was obtained by combined experimental and theoretical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
37
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 29 publications
5
37
2
Order By: Relevance
“…For comparison, the maximum value of ME coefficient obtained herein is about an order of magnitude higher than that (43 mV/cm·Oe at H dc = 134 Oe) reported by Wang et al for a 2.1 μm thick PZT film deposited on Metglas foil. Our ME coefficient value is also comparable to some of the best reported α ME for PZT‐based ME film composites …”
Section: Resultssupporting
confidence: 87%
“…For comparison, the maximum value of ME coefficient obtained herein is about an order of magnitude higher than that (43 mV/cm·Oe at H dc = 134 Oe) reported by Wang et al for a 2.1 μm thick PZT film deposited on Metglas foil. Our ME coefficient value is also comparable to some of the best reported α ME for PZT‐based ME film composites …”
Section: Resultssupporting
confidence: 87%
“…Although some previous studies have reported the development of PZT/Ni film-based ME composites, it has been challenging to achieve an appreciable ME output. [13][14][15] This can be attributed to the processing issues raised by the thermodynamic incompatibility between PZT and Ni. If no passivation layers are utilized during PZT film crystallization, the high temperatures required cause oxidation of Ni and interfacial chemical reactions between PZT and Ni; these complicate the strain transfer and impair the ME coupling.…”
mentioning
confidence: 99%
“…A comparison of the α ME values of various reported ME composites relevant to this work is shown in Table S1 of the supplementary material. [13][14][15][24][25][26][27]30 The α ME obtained from the (001) oriented PZT film on the Ni foil significantly outperforms that of all the ME film composites based on either PZT/Ni or textured PZT films deposited on magnetostrictive oxide substrates. The high piezoelectric response and the low dielectric constant, due to the strong texturing of the PZT grains and their domain state, presumably contributed to the larger ME output, since α ME ∝ g ij (=d ij /ε ij ), where ε ij is dielectric permittivity and g ij and d ij are piezoelectric voltage and charge coefficients, respectively.…”
mentioning
confidence: 99%
See 2 more Smart Citations